Changing teachers' work : the 'reform' of secondary schooling - Helsby, Gill. (Buckingham : Open University Press, 1999)
Changing discourses for new times. Changing teachers' work: structure, culture and agency. Changing frameworks, changing systems. Changing what teachers teach. Changing how teachers teach...
Keywords: Education; School management; High school teaching; Secondary education; Educational change; School organization; High school teaching -- Great Britain; Education, Secondary -- Great Britain; School management and organization -- Great Britain; Educational change -- Great Britain